2021
DOI: 10.1111/bju.15562
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implementation of pre‐biopsy magnetic resonance imaging pathways for the diagnosis of prostate cancer

Abstract: Objective To assess the outcomes of pre‐biopsy magnetic resonance imaging (MRI) pathways, as a tool in biopsy‐naïve men with suspicion of prostate cancer, in routine clinical practice. Secondary outcomes included a comparison of transrectal MRI‐directed biopsy (TR‐MRDB) and transperineal (TP)‐MRDB in men with suspicious MRI. Patients and Methods We retrospectively assessed a two‐centre cohort of consecutive biopsy‐naïve men with suspicion of prostate cancer who underwent a Prostate Imaging‐Reporting and Data S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…According to the EAU recommendation, 54% of men with intermediate or high risk will have Prostate Imaging-Reporting and Data System (PI-RADS) scores of 1–2 [1] , [14] . Similar rates (49–59%) have been reported by expert centers, but it should be noted that these percentages were from (screening) populations not yet stratified using pre-MRI risk assessment tools [13] , [15] , [16] . A recent Cochrane systematic review that also included centers with less prostate MRI expertise showed that the group of biopsy-naïve men with a clinical suspicion of PCa had a markedly lower PI-RADS 1–2 assessment rate (33%) [17] ; the prevalence of csPCa among studies included in the systematic review was 30%.…”
supporting
confidence: 82%
“…According to the EAU recommendation, 54% of men with intermediate or high risk will have Prostate Imaging-Reporting and Data System (PI-RADS) scores of 1–2 [1] , [14] . Similar rates (49–59%) have been reported by expert centers, but it should be noted that these percentages were from (screening) populations not yet stratified using pre-MRI risk assessment tools [13] , [15] , [16] . A recent Cochrane systematic review that also included centers with less prostate MRI expertise showed that the group of biopsy-naïve men with a clinical suspicion of PCa had a markedly lower PI-RADS 1–2 assessment rate (33%) [17] ; the prevalence of csPCa among studies included in the systematic review was 30%.…”
supporting
confidence: 82%
“…Wide variations in sensitivity and specificity can be explained by different acquisition protocols, different thresholds being applied, different reference criteria used, biopsy inaccuracies, and the varied experience levels of the radiologists with PI-RADS v2. Multiple guidelines have recommended the routine application of mpMRI in biopsy-naïve patients with suspected PCa, and there is an ongoing implementation process in clinical practice [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the biopsy route, the transperineal route benefits from reduced or no antibiotic prophylaxis and, therefore, has gained popularity owing to concerns on the transrectal route regarding sepsis [126][127][128] . Transperineal biopsy favours an improved sampling of the anterior part of the prostate 129 , and can also be implemented in an outpatient setting under local anaesthesia 130 . Thus, transperineal biopsy is gaining momentum, considering that the transperineal and the transrectal approaches offer equal cancer detection rates 131 .…”
Section: [H1] Variables Qa and Qc In Prostate Biopsymentioning
confidence: 99%